2012
DOI: 10.1136/bmj.e6457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intended intraoperative cholangiography and early detection of bile duct injury on survival after cholecystectomy: population based cohort study

Abstract: Objectives To determine whether the routine use of intraoperative cholangiography can improve survival from complications related to bile duct injuries.Design Population based cohort study.Setting Prospectively collected data from the Swedish national registry of gallstone surgery and endoscopic retrograde cholangiopancreatography, GallRiks. Multivariate analysis done by Cox regression. Population All cholecystectomies recorded in GallRiks between 1 May 2005 and 31 December 2010.Main outcome measures Evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
168
1
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(180 citation statements)
references
References 26 publications
4
168
1
7
Order By: Relevance
“…Even if QoL data was not reported this demonstrated that all postoperative complications must be promptly and properly managed if one is to avoid negative impact on outcome. 3,22 The reduced QoL reported here by patients being referred to tertiary referral centres is explained only in part by the severity of the injury and that the diagnosis was made postoperatively/late. In the Swedish context an intraoperative cholangiogram is standard which have resulted in an exceptionally high degree of intraoperative bile duct injury diagnosis.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Even if QoL data was not reported this demonstrated that all postoperative complications must be promptly and properly managed if one is to avoid negative impact on outcome. 3,22 The reduced QoL reported here by patients being referred to tertiary referral centres is explained only in part by the severity of the injury and that the diagnosis was made postoperatively/late. In the Swedish context an intraoperative cholangiogram is standard which have resulted in an exceptionally high degree of intraoperative bile duct injury diagnosis.…”
Section: Discussionmentioning
confidence: 80%
“…[1][2][3][4][5][6] The variation in frequency in the literature is mainly due to various ways of defining a BDI, i.e. if leakage from the cystic duct and liver bed is classified as a bile duct injury or not.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective studies might contain selection bias, thereby giving a too low incidence of injuries. In a prospective Swedish registry, the frequency of bile duct injuries was reported to be 1.5% which is much higher than the usually stated frequency of 0.2%-0.9% (16) . In our series, we found a frequency of 0.4% injuries of the main bile duct and 0.9% when cystic duct problems and aberrant ducts are included.…”
Section: Discussionmentioning
confidence: 93%
“…Several authors claimed that IOC cannot prevent BDI and its implication has yet to be defined [42, 43]. However, IOC is a definitive procedure to confirm BDI and may preclude further damage to the biliary system and surrounding vital vessels [44]. In the aforementioned SAGES survey, almost 90% of respondents agreed that "Surgeons should be able to perform and interpret IOC" [27].…”
Section: Discussionmentioning
confidence: 99%